Epigenetic Modifications and Diabetic Retinopathy. (28th October 2013) - Kowluru, Renu A.; Santos, Julia M.; Mishra, Manish
Abstract : Diabetic retinopathy remains one of the most debilitating chronic complications, but despite extensive research in the field, the exact mechanism(s) responsible for how retina is damaged in diabetes remains ambiguous. Many metabolic pathways have been implicated in its development, and genes associated with these pathways are altered. Diabetic environment also facilitates epigenetics modifications, which can alter the gene expression without permanent changes in DNA sequence. The role of epigenetics in diabetic retinopathy is now an emerging area, and recent work has shown that genes encoding mitochondrial superoxide dismutase ( Sod2 ) and matrix metalloproteinase-9 ( MMP-9 ) are epigenetically modified, activates of epigenetic modification enzymes, histone lysine demethylase 1 (LSD1), and DNA methyltransferase are increased, and the micro RNAs responsible for regulating nuclear transcriptional factor and VEGF are upregulated. With the growing evidence of epigenetic modifications in diabetic retinopathy, better understanding of these modifications has potential to identify novel targets to inhibit this devastating disease. Fortunately, the inhibitors and mimics targeted towards histone modification, DNA methylation, and miRNAs are now being tried for cancer and other chronic diseases, and better understanding of the role of epigenetics in diabetic retinopathy will open the door for their possible use in combating this blinding disease.